Constraints on gene patent protection fuel secrecy concerns: a qualitative study - Guerrini, Christi J (J Law Biosci, 2017)
Concern is mounting that innovators are responding to recent changes in patent eligibility by increasingly choosing to protect their discoveries as trade secrets. Due to the clandestine nature of trade secrets, it is impossible to quantify the extent to which innovators actually elect to protect their inventions as trade secrets rather than patents. Nevertheless, interest in each strategy may be gauged through qualitative means. We conducted semi-structured interviews of legal and scientific experts (n = 30) to understand the effect of recent patent eligibility changes on interest in patenting and trade secrecy of genetic innovations. Interview data indicate that secrecy may have increased in strategic appeal relative to patent protection in some areas of genetic innovation, although the actual election of secrecy strategies is often limited as a practical matter. The data also suggest that the burden of navigating the new intellectual property landscape may be falling disproportionately on those who translate gene-based discoveries into clinical applications. Some interviewees expressed concern about the normative implications of secrecy on advancements in and access to genetic medicine. Our findings are potentially relevant to policy proposals intended to restore some of the legal protection that was lost as a result of recent changes to patent eligibility, including amending the federal patent statute and expanding regulatory exclusivities for some genetic technologies.